Different individual areas of interaction and the effects on the behavior of players: applications to training in soccer - D. Casamichana; J. Castellano (Asociación Española de Ciencias del Deporte, 2010)
The small-sided games are situations commonly used in the training of soccer with physical, technical and/or tactical-strategic purposes. Those are held in different pitch dimensions, unkown altering the effect in the game. Therefore, the purpose of this study is to know the effects on the behavior of players and teams of one format of small-sided games where has been altered the individual space of interaction, keeping constant the variables: number of players, the presence of goalkeepers, availability of balls, encouragement of the coach and similar level of teams.           Were performed in three consecutive sessions three formats of small-sided games each of the individual space of interaction. Subsequently recorded the driving behavior of players using a tool designed for ad hoc observation, which before showed high stability between observations. Finally, carried out a series of descriptions and inferential analysis. The pitch dimensions of interaction in the task proposals affecting quality and quantity in the driving behavior of players, which have detected significant differences in the game. The individual space of interaction is an important variable to consider in the design of tasks for training in soccer. Key Words:soccer, small sided games, notation analysis, motor behaviour